Descriptive Analysis of Diabetic Retinopathy in Central Java Province (Case Study at RSUP Dr. Kariadi) - Casmuti, Casmuti; Cahyati, Widya Hary; Zainafree, Intan; Parno, Parno (Public Health Perspective Journal, 2024)
Diabetic retinopathy is a serious complication of diabetes that affects the blood vessels in the retina, leading to nutritional disorders. In Central Java Province, the prevalence of diabetes mellitus increased from 10% in 2022 to 12.52% in the third quarter of 2023; this phenomenon has not reached the SDG's target of zero increase. This study analyzes the frequency distribution of diabetic retinopathy cases at RSUP Dr. Kariadi Semarang in 2023. Using a cross-sectional design, this observational descriptive research utilized electronic medical record data from RSUP Dr. Kariadi Semarang in 2023. The study examined various variables, including gender, age, education level, employment status, marital status, BMI, DM diet, duration of DM, hypertension, other diseases, current blood glucose, and HbA1c. Univariate analysis was used to determine the frequency distribution and present graphical representations of each variable. The study's findings showed the largest percentage of diabetic retinopathy patients were female (54.2%), aged 50-59 years (48.8%), with low education (38.0%), working (66.3%), married (92.8%), and obese (18.7%). Most patients had a duration of DM ≥ 5 years (51.2%), hypertension (73.5%), and other diseases such as azotemia, CKD, cataracts, and cardiomegaly; patients had blood glucose at ≥ 200 mg/dL (53.0%) and HbA1c ≥ 6.5% (88.0%).